A Retrospective Study of Patients Undergoing Acute Electroconvulsive Therapy for Predominately Manic or Mixed Episodes With and Without Lithium in Singapore. Issue 4 (22nd December 2021) - Tang, Kai Wen Aaron; Tan, Xiao Wei; Tor, Phern-Chern
Abstract : Objective: The effect of lithium therapy during Electroconvulsive Therapy (ECT) on cognition and treatment effectiveness is unclear. In this study, we compare the cognitive and symptomatic outcomes of patients undergoing ECT with and without lithium in a large tertiary psychiatric institution. Methods: Patients with predominantly manic or mixed episodes on lithium were propensity score matched with controls. Cognition was assessed using the Montreal Cognitive Assessment (MoCA), while severity of symptoms was assessed using the Brief Psychiatric Rating Scale (BPRS) and Clinical Global Impression-Severity Scale. Quality of life was assessed using the Quality of Life Enjoyment and Satisfaction Questionnaire Short Form (Q-LES-Q-SF) and EuroQol Five Dimension (EQ-5D). Linear mixed-effects modeling and conditional logistic regression were conducted as appropriate. Results: 87 patients were included in the study. There was no significant difference in cognitive and symptomatic outcomes for patients receiving ECT with or without lithium after 6 sessions of ECT. Conclusions: Concurrent lithium administration during the initial acute ECT course was not associated with differential cognitive or symptomatic outcomes. Lithium administration should not be a contraindication for appropriate acute ECT treatment in patients. Larger controlled studies to confirm these findings are warranted.